Counseling on Hypertension in the Elderly in Lubuk Raya Village in 2024 - Siregar, Rya Anastasya; Batubara, Novita Sari; Said, Arisa Harfa; Harahap, Maryam Latifah; Siregar, Rahmah Juliani (IJCS: International Journal of Community Service, 2024)
The elderly are an age group that is vulnerable to various health problems. Classification of the elderly According to WHO, an elderly person is someone who has reached the age of 60 years and above. Hypertension is a high blood pressure disease whose prevalence is still high in Indonesia. According to data from the Ministry of Health, the prevalence of hypertension in Indonesia itself reaches 34.11% of the population. Factors that influence the incidence of hypertension include genetics, race, regional, socio-culture which also relate to different lifestyles so that the incidence rates vary. The form of this activity is counseling to the community with lecture methods, discussions and demonstrations equipped with various media and snack distribution. Results: Based on the evaluation results, the elderly have understood what has been conveyed. It is expected that the community will control their blood pressure regularly every day.